Integrating Pancasila in Character Education: A Qualitative Analysis of Ethical Values for Nation-Building - Farwati, Sizka; Iskhak, Muhamad; Nunu Mahnun (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research delves into the critical role of Pancasila, the philosophical foundation of Indonesia, in shaping character education within the nation. Utilizing a qualitative descriptive methodology, predominantly through extensive literature reviews, the study investigates how Pancasila's core ethical values significantly influence character development. Emphasizing the integration of Pancasila's principles—Belief in the Divine, Just, and Civilized Humanity, Unity of Indonesia, Democracy led by the Wisdom of Deliberations among Representatives, and Social Justice for all Indonesians—this research underscores their essentiality in instilling moral and ethical consciousness in Indonesia's diverse populace. Key findings reveal the effectiveness of the threefold strategy of